Effect of chitin amendment on soil microflora relation to chitinase activity and its effect on survival of Fusarium moniliforme - D.N. MANDAL, S. CHAUDHURI and (Indian Phytopathology, 2002)
Amendment of soil with chitin favoured the increase in the number of chitinase producing members of the soil microflora. Chitinase extracted from these members was however found to have no role to play in the lysis of live mycelium of Fuasrium moniliforme under in vitro conditions, though there was partial lysis of dead germ tubes. Results indicate the quantity of extracellular chitinase produced by the soilmicro-organisms is not a critical factor in determining their mycolytic ability.